Tantangan Guru EFL dalam Konteks Pembelajaran Berbasis Proyek di Kelas 3 dan 4 di Sekolah Pelangi Bali - Dwiyanti, Kadek Natalia; Utami, IGA Lokita Purnamika; Adnyayanti, Ni Luh Putu Era (Universitas Pendidikan Ganesha, 2024)
Education in the 21st-century requires students to have learning and innovation skills, knowledge, media and technology skills, as well as life and career skills. To meet these demands, an appropriate curriculum is needed, one of which is the Merdeka Curriculum. One of the learning models that supports the implementation of the Merdeka Curriculum is Project-Based Learning (PjBL). PjBL is one of the student-centered learning models. PjBL emphasizes students to be collaborative, creative and able to think critically. This research was conducted to find out the problems encountered by teachers in implementing Project-Based Learning. This research used a case study using a descriptive qualitative approach. In collecting data, this study used two instruments, namely observation checklist when conducting observations and also interviews to strengthen the findings obtained during observation. This research was conducted at Pelangi School Bali. The subjects of this research were a teacher in grade 3 and two teachers in grade 4. The results of this research show that the most common obstacle experienced by teachers is time management.